2017
DOI: 10.1590/s2175-97902017000116109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potential drug-drug interactions in the intensive care unit of a Brazilian teaching hospital

Abstract: Patients in intensive care unit are prescribed large numbers of drugs, highlighting the need to study potential Drug-Drug Interactions in this environment. The aim of this study was to delineate the prevalence and risk of potential drug-drug interactions between medications administered to patients in an ICU. This cross-sectional observational study was conducted during 12 months, in an adult ICU of a teaching hospital. Inclusion criteria were: prescriptions with 2 or more drugs of patients admitted to the ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
2
9

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 28 publications
7
20
2
9
Order By: Relevance
“…Other studies in surgical departments are few. A Brazilian study of drug interactions in the ICU reported a higher prevalence of pDDIs which was 89% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in surgical departments are few. A Brazilian study of drug interactions in the ICU reported a higher prevalence of pDDIs which was 89% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pDDIs among patients in surgery departments may have unique interactions compared to patients hospitalized in other hospital departments. Little is known about pDDIs in surgery departments [ 18 , 19 ]. In addition, data regarding drug interaction potential in Palestine hospitals is scarce [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They identified the interaction between dipyrone, and enoxaparin (35.8%) was the most prevalent. [ 26 ] In our study, we noticed, 76.9% major and 16.9% moderate DDIs. Most of the significant drug interactions occurred with ondansetron comprising 38%.…”
Section: Discussionmentioning
confidence: 52%
“…More than 16 million people were estimated to have diabetes in the AFRO Region and the figure is expected to increase to 41 million to by the year 2045 (IDF, 2016). Polypharmacy is common in clinical practice (Greenblatt et al, 2017;Rodrigues et al, 2017). The chronic treatment with one drug may be supplemented by a further short-term treatment with a second drug, or several drugs may be co-administered on a long-term basis (Greenblatt et al, 2017;Rodrigues et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy is common in clinical practice (Greenblatt et al, 2017;Rodrigues et al, 2017). The chronic treatment with one drug may be supplemented by a further short-term treatment with a second drug, or several drugs may be co-administered on a long-term basis (Greenblatt et al, 2017;Rodrigues et al, 2017). In malarial endemic areas, the need for polypharmacy for diabetic patients becomes obvious in majority of patients (Greenblatt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%